2017
DOI: 10.1097/id.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Bone Regeneration by Conditioned Medium From Mesenchymal Stem Cells After Maxillary Sinus Floor Elevation

Abstract: The secretome of bone marrow-derived mesenchymal stem cells (MSC-CM) was used safely and has great osteogenic potential for regenerative medicine of bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 29 publications
1
50
0
1
Order By: Relevance
“…The study revealed a significant increase in bone formation, with respect to bone volume in the individuals treated with BMSC‐CM. The positive effects observed during the study were attributed towards the presence of IGF‐1, TGF‐β1 and VEGF of the BMSC secretome (Katagiri et al, ). BMSC‐CM have also been used in combination with BMSCs for phase I/IIa clinical trials for the treatment of multiple sclerosis.…”
Section: Paracrine Action Of Conditioned Media In Clinical Applicationsmentioning
confidence: 99%
“…The study revealed a significant increase in bone formation, with respect to bone volume in the individuals treated with BMSC‐CM. The positive effects observed during the study were attributed towards the presence of IGF‐1, TGF‐β1 and VEGF of the BMSC secretome (Katagiri et al, ). BMSC‐CM have also been used in combination with BMSCs for phase I/IIa clinical trials for the treatment of multiple sclerosis.…”
Section: Paracrine Action Of Conditioned Media In Clinical Applicationsmentioning
confidence: 99%
“…This concept is based on observations that a very small fraction of implanted MSCs survives long enough in vivo to differentiate, suggesting that MSCs mainly exert their regenerative effects via paracrine mechanisms (Haumer et al., ). Following promising pre‐clinical results, one group has recently reported the clinical application of allogeneic MSCs conditioned medium, in combination with β‐TCP or COL sponge scaffolds, for bone regeneration in SA, RA and SP, in nine patients with favourable outcomes and no adverse events (Katagiri, Osugi, Kawai, & Hibi, ; Katagiri et al., ). The safety and efficacy of allogeneic MSCs secretome (lyophilised) as an “off‐the‐shelf” therapy for bone regeneration should be investigated in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Secretome-based approaches using CM may present osteogenic potential advantages over living cells regarding manufacturing, storage, handling, product shelf life and their potential as a ready-to-go biological therapeutic agent [34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%